Human small intestinal organotypic culture model for drug permeation, inflammation, and toxicity assays - Markus, Jan (In Vitro Cell Dev Biol Anim, 2020)
The gastrointestinal tract (GIT), in particular, the small intestine, plays a significant role in food digestion, fluid and electrolyte transport, drug absorption and metabolism, and nutrient uptake. As the longest portion of the GIT, the small intestine also plays a vital role in protecting the host against pathogenic or opportunistic microbial invasion. However, establishing polarized intestinal tissue models in vitro that reflect the architecture and physiology of the gut has been a challenge for decades and the lack of translational models that predict human responses has impeded research in the drug absorption, metabolism, and drug-induced gastrointestinal toxicity space. Often, animals fail to recapitulate human physiology and do not predict human outcomes. Also, certain human pathogens are species specific and do not infect other hosts. Concerns such as variability of results, a low throughput format, and ethical considerations further complicate the use of animals for predicting the safety and efficacy xenobiotics in humans. These limitations necessitate the development of in vitro 3D human intestinal tissue models that recapitulate in vivo–like microenvironment and provide more physiologically relevant cellular responses so that they can better predict the safety and efficacy of pharmaceuticals and toxicants. Over the past decade, much progress has been made in the development of in vitro intestinal models (organoids and 3D-organotypic tissues) using either inducible pluripotent or adult stem cells. Among the models, the MatTek’s intestinal tissue model (EpiIntestinal™ Ashland, MA) has been used extensively by the pharmaceutical industry to study drug permeation, metabolism, drug-induced GI toxicity, pathogen infections, inflammation, wound healing, and as a predictive model for a clinical adverse outcome (diarrhea) to pharmaceutical drugs. In this paper, our review will focus on the potential of in vitro small intestinal tissues as preclinical research tool and as alternative to the use of animals.